FIRST OCCURENCE OF CAULERPA MACRODISCA (CAULERPACEAE, CHLOROPHYTA) IN MALAYSIA BASED ON THE MOLECULAR AND MORPHOLOGICAL EVIDENCE - Zuldin, Wahidatul Husna; Shapawi, Rossita; Muhamad Shaleh, Sitti Raehanah; Abdul Kadar, Nazia; Muhammad Lal, Muhammad Tamrin (Malaysian Journal of Science, 2019)
The siphonous green macroalgae Caulerpa macrodisca (Decaisne) Weber-van Bosse has been reported to be widely distributed around South-west Asia (Sri Lanka), South China Sea, South-east Asia (Indonesia, Philippines, Singapore and Vietnam) and Pacific Islands (Samoan Archipelago). There was no formal report on the existence of C. macrodisca in Malaysia. This study reported the first occurence of the green algae, C. macrodisca in the coastal area of Menumbok, Sabah, Malaysia. The C. macrodisca was first discovered in March 2016 grew around the sea cage of a local farmer in Sikalong Village, Menumbok. In May and July 2016, C. macrodisca was searched around the coastal area near the sea cage and the existence was discovered at 1.4 to 2.7 m depth. Further scuba search was done in August 2016 and confirmed the occurrence nearby the area at similar depth. Most of the collected green macroalgae were large and reproductive and a few were small and young but precociously reproductive. The samples were collected in May, July and August 2016 for further analysis. The collected specimen was confirmed as C. macrodisca through morphology and genetic analyses using tufA gene as DNA biomarker. In conclusion, the first occurrence of C. macrodisca in Malaysia added a new record for the South China Sea region marine algae checklist.